Using C++ std::bind and std::function - Caisse, Michael; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"Forwarding call wrappers and function wrappers provide an elegant solution to many problems involving interfaces and callbacks. In this webcast we will explore how to employ std::bind and std::function to write better, decoupled code. Participants will learn: what a functor is and why it is useful, how to bind call arguments of all flavors, how to use placeholders and adapt interfaces, how to store callable things based on their signature, how to create better interfaces with std::bind and std::function."--Resource description page.
Title from title screen (viewed July 22, 2015)
Date of publication taken from resource description page.
Presenter, Michael Caisse.
Keywords: C++ (Computer program language); Object-oriented programming languages; Electronic books